SOEPP-SuBROUTINE ORIENTED ENVIRONMENT IN PARALLEL PROGRAMMING (Biological Sciences - PJSIR, 2002)
Generally, the software for real time parallel processing comprises of system software and the application software.  The  system software, in turn , comprises a run time executive and a parallel compiler for high-level language interface. This paper presents a novel approach to the design of run time support software and a parallel compiler to facilitate the user with a Subroutine Oriented Environment in Parallel Programming. Using this environment, the user is able to upgrade the parallel processor system for more power and bandwidth by adding more processor boards in the system architecture  without modifying  or  recompiling  the  system  or  the  applications software.